Performance Study of multistage membrane and hybrid distillation processes for propylene/propane separation. (26th July 2017) - Park, Jaedeuk; Kim, Kiwoong; Shin, Jae‐Wook; Tak, Kyungjae; Park, Yong‐Ki
Abstract : This article investigates the separation performance and energy efficiency of multistage membrane and hybrid processes for the separation of propane/propylene mixtures compared with the conventional distillation process. To satisfy the separation objective of 0.996 mol/mol (99.6 mol%) C3 H6 purity and 97 % C3 H6 separation recovery ratio, a detailed parametric study for the multistage membrane and hybrid process systems was described. For this purpose, the effects of operating conditions and process configurations on separation performance have been evaluated using a counter‐current flow model. The numerical model using a single‐stage membrane was validated with published experimental data for the membrane system, and the model was then applied to multistage membrane and hybrid processes. The optimum variables that satisfy the targeted purity and recovery ratio were examined using the multistage membrane at a given selectivity and pressure ratio. The energy consumption of several hybrid configurations for the separation of propane/propylene mixtures was investigated with conventional distillation.